PENGARUH VARIASI DOSIS LARUTAN BUAH BELIMBING WULUH (Averrhoa bilimbi L.)TERHADAP MORTALITAS LARVA NYAMUK Culex sp. SEBAGAI SUMBER BELAJAR BIOLOGI PADA MATERI INSEKTA - Sidik, Bagas Rasid (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
Control of larvae of Culex sp. can be done with larvicides. Larvicides used in an attempt to reduce the population of larvae in a breeding place or for termination of the chain of mosquito breeding. Insect repellent effective to kill mosquitoes, but that has not been come mosquito larvae will develop into mosquitoes. Insect repellent made from synthetic chemicals if used excessively will cause adverse effects to humans such as respiratory disorders, digestive, and the environment. The purpose of this study was to determine (1) Whether or not the effect of giving a solution of fruit starfruit (Averrhoa bilimbi, L.) against Culex sp. mosquito larvae mortality, (2) determine the most appropriate dosage on mortality of larvae of mosquito Culex sp., (3 ) Compile the results of the research as a high school biology class X LKPS semester two. This study uses the method of experiment, the draft design used was completely randomized design Variety (CRD) with the control (P0) and 4 treatments, namely P1: a dose of1/99 ml, P2: dose2/98 ml, P3: dose3/97 ml, and P4: a dose4/96 ml with 6 replicates each, the number of larvae 150 animals. Larva l sampling and testing conducted at Flores Street No. 19 Ganjar Supreme 14/2 City Metro. The test was analyzed using one-way Anava non-parametric Kruskall-Wallis test. The results of the analysis are obtained as follows: (1) There is a very significant influence on the administration of a solution of fruit starfruit (Averrhoa bilimbi, L.) against Culex mosquito larvae mortality due to the α sp 0.05, at α 0.01 in Chi-square table, (2) the mortality of larvae of Culex for 24 consecutive hour sare from lowest to highest mortality percentage is P0=0%, P1=60%, P2=83.33%, 83.33% =P3, andP4=86,66%. Based on the results of research and discussion we concluded that: (1) There is the effect of star fruit solution on mortality of larvae of Culex sp mosquitoes, with coefficientH=17.73>Chi-square value of7.81at α level of 0.05, 11, 3 Dapaαlevelof 0.01., (2) At a dose of4/96 ml solution starfruit is the best dosage on mortality of larvae of mosquito Culex sp., (3) the results of this studying the form of LKPS (Practical Guidelines Worksheet) can support (KI) and (KD) in the curriculum syllabus 2013.Kata Kunci: Variasi dosis, larutan belimbing wuluh, Mortalitas, larva nyamuk Culex sp., sumber belajar biologi.